Meninjau Kembali Teori Utang Publik Dan Pertumbuhan Ekonomi - Safa Kharisma; Aminudin Ma'ruf (Universitas Negeri Surabaya, 2026)
Public debt is one of the fiscal policy instruments used by the government to close the deficit, finance development and stabilize the economy. However, the relationship between public debt and economic growth is still a matter of debate in the economic literature. This study aims to review the relationship between public debt and economic growth with an emphasis on a theory-based approach. The method used is a systematic literature review (SLR) of international journal articles published. This study groups research findings based on the main theoretical framework, namely neoclassical, keynesian, debt overhang, ricardian equivalence, and endogenous growth. The results of the review show that the influence of public debt on economic growth is contextual and influenced by the quality of institutions, debt structure, economic conditions and the effectiveness of government spending. In general, public debt tends to have a negative impact on growth when it has crossed the limit, but it can be neutral or even positive under certain conditions. This article contributes by presenting a comprehensive theoretical synthesis, providing direction for empirical research and the formulation of fiscal policy going forward.